2022
DOI: 10.3390/jfmk7040111
|View full text |Cite
|
Sign up to set email alerts
|

Investigating External and Internal Loads in Male Older Adult Basketball Players during Official Games

Abstract: This study aimed at assessing the external [Player Load (PL), acceleration (ACC), changes of direction (COD), JUMP, and their relative values (PL/min; ACC/min; COD/min and JUMP/min)] and internal [percentage of the peak heart rate (%HRpeak) and the training load calculated with the session rating of perceived exertion (sRPE) method (sRPE-load)] loads of masters (senior citizen) basketball players during official games. Thirteen male basketball masters players (age: 66.6 ± 2.1 years; body mass: 89.9 ± 8.7 kg; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…The safety and first aid content unit mainly regarded past and present medical conditions (numbers 11 and 12), nutritional habits (numbers 13 and 14), and safety measures (numbers 15 and 16). Statements related to physiology and fitness mainly concerned functional fitness and its evaluation (numbers [17][18][19][20][21][22][23][24][25][26] and two items related to general and judo-specific literacy (numbers 27 and 28). The statements associated with psychology and mental health encompassed psychological personal traits, characteristics, and disorders (numbers 29-33), self-related aspects (numbers 34 and 35), cognition and motivation (numbers 36 and 37), and concerns (numbers 38 and 39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and first aid content unit mainly regarded past and present medical conditions (numbers 11 and 12), nutritional habits (numbers 13 and 14), and safety measures (numbers 15 and 16). Statements related to physiology and fitness mainly concerned functional fitness and its evaluation (numbers [17][18][19][20][21][22][23][24][25][26] and two items related to general and judo-specific literacy (numbers 27 and 28). The statements associated with psychology and mental health encompassed psychological personal traits, characteristics, and disorders (numbers 29-33), self-related aspects (numbers 34 and 35), cognition and motivation (numbers 36 and 37), and concerns (numbers 38 and 39).…”
Section: Resultsmentioning
confidence: 99%
“…In this framework, older individuals are recommended to engage >2 days weekly in a multi-component physical activity, encompassing both aerobic exercise and resistance training involving major muscle groups, complemented by the combination of exercise and cognition (e.g., dual tasks) [ 4 , 13 , 14 ]. Furthermore, physically active older individuals are considered good examples of successful aging, and the involvement of older people in sport-based programs resulted in particularly effective in preserving their health with advancing years [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Support can emerge from personal, family, and social spheres highlighting the possible benefits of judo with advancing age [ 2 , 21 ]. To motivate the practitioners, recognise their competence, autonomy, and relatedness, judo coaches should possess specific hard (e.g., judo knowledge) and soft (e.g., communication, problem solving) skills [ 10 , 15 , 42 ]. Furthermore, judo can become an extraordinary means of transgenerational connections, where young and older practitioners share their unique knowledge and abilities for a mutual enrichment [ 27 , 37 , 40 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, training programs for older people should combine exercise and cognition (e.g., dual tasks) [ 7 , 13 ]. In this framework, sport-based interventions proved to be particularly effective [ 3 , 12 , 14 , 15 , 16 ], with master athletes considered good examples of successful aging for preserving high levels of fitness, performances, mental health, social interactions, and quality of life, as well as experiencing low levels of stress, negative feelings, and depression [ 3 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While commonly being used in volleyball (Cabarkapa et al, 2022), Benson et al (2020) found that the same device was a reliable and appropriate testing modality for estimating jump load in youth basketball players during both game and practice sessions. However, it should be noted that usage of other IMU technologies (e.g., Catapult TM ) for monitoring the athletes' workloads has been more prevalent in basketball (Conte et al, 2022;Scanlan et al, 2014;Schelling & Torres, 2016;Svilar et al, 2018a). For example, Svilar et al (2018a) used a tri-axial accelerometer technology (i.e., Catapult TM ) and session RPE to quantify both external and internal loads in professional male basketball athletes playing at some of the top levels of competition in Europe (e.g., ACB League, Euroleague).…”
Section: Discussionmentioning
confidence: 99%